2014
DOI: 10.1115/1.4027316
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cycle Fatigue of Pressurized Steel Elbows Under In-Plane Bending

Abstract: The present study examines the mechanical behavior of steel process piping elbows, subjected to strong cyclic loading conditions. The work is numerical, supported by experimental data on elbow specimens subjected to in-plane cyclic bending, with or without internal pressure, resulting in failure in the low-cycle-fatigue range. The investigation of elbow behavior is conducted using rigorous finite element analysis accounting for measured elbow geometry and the actual material properties. An advanced cyclic plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…The fabricated elbow specimens with local wall thinning were subjected to displacement-controlled loading conditions (± 20 mm) until failure. Similar loading conditions have also been utilized in previous studies providing the fatigue life of elbows between 50 and 500 cycles [1]. The present experimental studies were supported by high-fidelity finite element (FE) simulations, which identified main deformation and failure mechanisms.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…The fabricated elbow specimens with local wall thinning were subjected to displacement-controlled loading conditions (± 20 mm) until failure. Similar loading conditions have also been utilized in previous studies providing the fatigue life of elbows between 50 and 500 cycles [1]. The present experimental studies were supported by high-fidelity finite element (FE) simulations, which identified main deformation and failure mechanisms.…”
Section: Introductionsupporting
confidence: 58%
“…As elbows are very flexible and, when subjected to extreme loading condition, these structural elements can demonstrate cross-sectional ovalization and local buckling as well as failure in the form of cross-thickness cracking. It was also reported that multi-axial stress state due to bending and internal pressure can lead to reduction of fatigue life [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karamanos et al (2003Karamanos et al ( , 2006 have presented numerical studies for pressurized and non-pressurized steel elbow response under in-plane and out-of-plane bending, with emphasis on the buckling failure, and a good comparison between numerical results and the test data reported in was found. More recently, in the course of European research program INDUSE (Pappa et al 2013), motivated by the seismic integrity of industrial plants, the response of pipe elbows under strong cyclic loading has been investigated (Varelis et al 2013;Varelis and Karamanos 2015) experimentally, conducting tests on 8-inch-diameter SCH40 long radius 90°X52 elbows, leading to low-cycle fatigue fracture. The tests in Varelis et al (2013) and Varelis and Karamanos (2015) were also supported by extensive numerical simulations that employed advanced cyclic plasticity models, also reported in Varelis et al (2013) and Varelis and Karamanos (2015), and simplified analytical methodologies for the low-cycle fatigue design of the elbows.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in the course of European research program INDUSE (Pappa et al 2013), motivated by the seismic integrity of industrial plants, the response of pipe elbows under strong cyclic loading has been investigated (Varelis et al 2013;Varelis and Karamanos 2015) experimentally, conducting tests on 8-inch-diameter SCH40 long radius 90°X52 elbows, leading to low-cycle fatigue fracture. The tests in Varelis et al (2013) and Varelis and Karamanos (2015) were also supported by extensive numerical simulations that employed advanced cyclic plasticity models, also reported in Varelis et al (2013) and Varelis and Karamanos (2015), and simplified analytical methodologies for the low-cycle fatigue design of the elbows. For an overview on the mechanical behavior of steel pipe bends, the reader is referred to the recent paper by Karamanos (2016).…”
Section: Introductionmentioning
confidence: 99%